Regulation of Sclerostin Expression in Multiple Myeloma by Dkk‐1: A Potential Therapeutic Strategy for Myeloma Bone Disease. (19th February 2016) - Eda, Homare; Santo, Loredana; Wein, Marc N; Hu, Dorothy Z; Cirstea, Diana D; Nemani, Neeharika; Tai, Yu‐Tzu; Raines, Sarah E; Kuhstoss, Stuart Allen; Munshi, Nikhil C; Kronenberg, Henry M; Raje, Noopur S
ABSTRACT: Sclerostin is a potent inhibitor of osteoblastogenesis. Interestingly, newly diagnosed multiple myeloma (MM) patients have high levels of circulating sclerostin that correlate with disease stage and fractures. However, the source and impact of sclerostin in MM remains to be defined. Our goal was to determine the role of sclerostin in the biology of MM and its bone microenvironment as well as investigate the effect of targeting sclerostin with a neutralizing antibody (scl‐Ab) in MM bone disease. Here we confirm increased sclerostin levels in MM compared with precursor disease states like monoclonal gammopathy of undetermined significance (MGUS) and smoldering MM. Furthermore, we found that a humanized MM xenograft mouse model bearing human MM cells (NOD‐SCID.CB17 male mice injected intravenously with 2.5 million of MM1.S‐Luc‐GFP cells) demonstrated significantly higher concentrations of mouse‐derived sclerostin, suggesting a microenvironmental source of sclerostin. Associated with the increased sclerostin levels, activated β‐catenin expression levels were lower than normal in MM mouse bone marrow. Importantly, a high‐affinity grade scl‐Ab reversed osteolytic bone disease in this animal model. Because scl‐Ab did not demonstrate significant in vitro anti‐MM activity, we combined it with the proteasome inhibitor carfilzomib. Our data demonstrated that this combination therapy significantly inhibited tumor burden and improved bone disease in our in vivo MM mouse model. In agreement with our in vivo data, sclerostin expression was noted in marrow stromal cells and osteoblasts of MM patient bone marrow samples. Moreover, MM cells stimulated sclerostin expression in immature osteoblasts while inhibiting osteoblast differentiation in vitro. This was in part regulated by Dkk‐1 secreted by MM cells and is a potential mechanism contributing to the osteoblast dysfunction noted in MM. Our data confirm the role of sclerostin as a potential therapeutic target in MM bone disease and provides the rationale for studying scl‐Ab combined with proteasome inhibitors in MM. © 2016 American Society for Bone and Mineral Research.